Suhaib Al-Saqar’s approach to criticizing Muhammad Shahrour’s thought on the issue of the definitive and ambiguous books - Biaism Tah Eabdallah; Muhammad Hadi Shehab (Islamic Sciences Journal, 2025)
ABSTRACT In this research, Suhaib Al-Saqqar focuses on criticizing Muhammad Shahrur's interpretation of the terms "muhkam" and "mutashabih" in the Qur'an, discussing Shahrur's views, which he presented in the context of his contemporary reading. Al-Saqqar offers a methodological critique of these interpretations, demonstrating their contradictions and their impact on the understanding of the Qur'anic texts. Al-Saqqar criticized Muhammad Shahrur's construction of the terms "muhkam" and "mutashabih" in the Qur'an by raising several methodological and linguistic objections, indicating that Shahrur's interpretation is inconsistent with the traditional understanding of the Qur'an and is not based on sound Sharia evidence.